Consumer price behavior in Mexico under inflation targeting: A microdata approach - Carla Ysusi (Banco de México, 2010)
In this paper we do a statistical analysis of the Mexican Consumer Price Index microdata set to characterize the rigidities of the price setting process in the different sectors of the Mexican economy. The microdata set goes from July 2002 to December 2009. Broadly, results show that there exists a considerable heterogeneity in the price setting behavior across different sectors and over time. Evidence was found that when big shocks affect inflation, there is a strong co-movement of the fraction of the firms that change prices with the level of inflation.
Keywords: C19; E31; 330; Consumer Price Index; price setting process; frequencies and magnitudes of price changes; Verbraucherpreisindex; Mikrodaten; Betriebliche Preispolitik; Preisrigidität; Inflationssteuerung; Mexiko